Antibacterial evaluation of activated carbon cloth with Ag+ impregnated with ZnO nanoparticles. (9th September 2019) - Sharifuddin, Sharifatul Ain Binti; Ismail, Salwani Binti; Abdullah, Imran; Mohamad, Irfan; Shaikh Mohammed, Javeed
Abstract : Purpose: Staphylococcus aureus ( S. aureus ), Klebsiella pneumoniae ( K. pneumoniae ) and Streptococcus pneumoniae ( S. pneumoniae ) are among the pathogens detected during Hajj pilgrimage known to cause pneumonia. This study aims to evaluate the antibacterial activity of activated carbon cloth (ACC) with Ag + impregnated with zinc oxide nanoparticles (ZnO NPs) against these pathogens. Design/methodology/approach: ZnO NPs were impregnated into ACC-Ag + via layer-by-layer (LbL) self-assembly. Scanning electron microscope (SEM) was used to observe the fine surface morphological details of the ACC-Ag + -ZnO sheets. Antibacterial activity of the ACC-Ag + -ZnO sheets was evaluated using the disk-diffusion susceptibility assay. Allergy patch test was done to evaluate allergic reactions of the ACC-Ag + -ZnO sheets on human skin. Findings: SEM micrographs showed successful impregnation of ZnO NPs into the ACC-Ag + sheets. Disk-diffusion susceptibility assay results of ACC-Ag + -ZnO sheets against S. aureus, K. pneumoniae and S. pneumoniae showed good antibacterial activity; with 1.82 ± 0.13 mm zone of inhibition for S. pneumoniae, at a ZnO concentration of 0.78 mg mL -1 . No signs of human skin irritation were observed throughout the allergy patch test. Originality/value: Results indicate that ACC-Ag + -ZnO sheets could potentially be embedded within surgical face masks (pilgrims' preferred) to reduce the risks involved with the transmission of respiratory tract infections during and after mass gatherings (e.g. Hajj/Umrah, Olympics).